2010
DOI: 10.1097/bsd.0b013e3181b63d89
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dynesys System Screw Profile on Adjacent Segment and Screw

Abstract: This study found that the Dynesys system was able to restore spinal stability and alleviate loading on disc and facet at the surgical level, but greater ROM, annulus stress, and facet loading were found at the adjacent level. In addition, profile of the screw placement caused only a minor influence on the ROM, annulus stress, and facet loading, but the screw stress was noticeably increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 41 publications
5
32
0
Order By: Relevance
“…Our earlier study evaluated whether various depths of Dynesys screw placement would affect the biomechanical characteristics of the lumbar spine. We demonstrated that the profile of screw placement only had a minor influence on the ROM, annulus stress, and facet joint force, but that the screw stress was noticeably increased as the screw was moved further out of the pedicle [15].…”
Section: Introductionmentioning
confidence: 85%
“…Our earlier study evaluated whether various depths of Dynesys screw placement would affect the biomechanical characteristics of the lumbar spine. We demonstrated that the profile of screw placement only had a minor influence on the ROM, annulus stress, and facet joint force, but that the screw stress was noticeably increased as the screw was moved further out of the pedicle [15].…”
Section: Introductionmentioning
confidence: 85%
“…Kim et al (35) observed through x-ray evaluation in 31 patients that the dynamic stabilization preserves only a limited motion, and may cause stress on the adjacent above level. Liu et al (13), through finite element analysis, evaluated the mechanical behavior of the lumbar spine after insertion of the Dynesys system: they found that under flexion and lateral bending, it alleviated annulus stress at the surgical level, but increased it at the adjacent level. In the same way, under extension, it decreased facet loading at the surgical level but increased facet loading at the adjacent level.…”
Section: Discussionmentioning
confidence: 99%
“…However, discordant findings were found using this treatment, as it did not always result in clinical improvement (7)(8)(9)(10)(11)(12). In fact a high incidence of accelerated disc degeneration at adjacent levels has been reported when patients were treated with a rigid instrumentation system (13)(14)(15).…”
mentioning
confidence: 98%
“…7 Several researchers have investigated facet joint contact force in nonfusion dynamic stabilization, and the Dynesys system is reported to produce a greater facet contact force than that in the normal spine under all loading conditions. 11,14,16 A biomechanical FEM-based study of the Dynesys system at L4-5 showed that the facet contact force during extension increased with an increase in moment. 7 This undesirable effect on facet contact force would contribute to facet joint degeneration at the instrumented segment.…”
Section: Discussionmentioning
confidence: 99%